Fast-forward approach of time-domain NMR relaxometry for solid-state chemistry of chitosan. (15th March 2021) - Facchinatto, William Marcondes; dos Santos Garcia, Rodrigo Henrique; dos Santos, Danilo Martins; Fiamingo, Anderson; Menezes Flores, Douglas William; Campana-Filho, Sérgio Paulo; de Azevedo, Eduardo Ribeiro; Colnago, Luiz Alberto
Highlights: Degree of acetylation and crystallinity of chitosan can be evaluated by TD-NMR. RK-ROSE signal decay is mainly associated with the methyl hydrogens of GlcNAc units of chitosan chain. The rigid and mobile-part signals are modulated by the local chain packing. Abstract: Chitosans with different average degrees of acetylation and weight molecular weight were analyzed by time-domain NMR relaxometry using the recently proposed pulse sequence named Rhim and Kessemeier - Radiofrequency Optimized Solid-Echo (RK-ROSE) to acquire 1 H NMR signal of solid-state materials. The NMR signal decay was composed of faster (tenths of μs) and longer components, where the mobile-part fraction exhibited an effective relaxation transverse time assigned to methyl hydrogens from N -acetyl-d -glucosamine (GlcNAc) units. The higher intrinsic mobility of methyl groups was confirmed via DIPSHIFT experiments by probing the 1 H- 13 C dipolar interaction. RK-ROSE data were modeled by using Partial Least Square (PLS) multivariate regression, which showed a high coefficient of determination ( R 2 > 0.93) between RK-ROSE signal profile and average degrees of acetylation and crystallinity index, thus indicating that time-domain NMR consists in a promising tool for structural and morphological characterization of chitosan.